An evaluation of fetal heart rate characteristics associated with neonatal encephalopathy: a case‐control study. (15th April 2018) - Frey, HA; Liu, X; Lynch, CD; Musindi, W; Samuels, P; Rood, KM; Thung, SF; Bakk, JM; Cheng, W; Landon, MB
Abstract : Objective: We sought to identify fetal heart rate (FHR) characteristics that are associated with neonatal encephalopathy (NE). Design: Retrospective case‐control study. Setting: A single medical centre in Shanghai, China, 2006–2015. Sample: Women delivering a singleton, non‐anomalous infant at ≥36 weeks' gestation diagnosed with NE (cases, n = 109) were compared with a group of women with unaffected infants (controls, n = 233). Methods: Two physicians blinded to the outcome independently reviewed FHR tracings during the last 30 minutes of tracing prior to delivery. FHR characteristics were compared in the two groups and multivariable logistic regression was used to adjust for confounding. Main outcome measures: Adjusted odds ratio (aOR) and 95% confidence interval (CI) for the presence of specific FHR categories and characteristics. Results: Category II FHR tracings were observed in 89% of women prior to delivery and were not independently associated with NE. Notably, a category III FHR was observed in 17.4% of women in the NE group compared with 0.9% of women in the control group (aOR 44.99, 95% CI 7.23–279.97). Bradycardia, minimal/absent variability, late decelerations and prolonged decelerations were independently associated with NE, whereas accelerations were protective. Similar findings were found when the cases were limited to NE with arterial cord pH <7.1 and in a subgroup analysis of women with category II tracings. Conclusions: Category III tracings, while infrequent, are not uncommon prior to delivery among fetuses who develop NE. In contrast, most FHR tracings are category II prior to delivery; however, individual FHR characteristics within this category are associated with NE. Funding: This research was supported by the Interdisciplinary Programme of Shanghai Jiao Tong University. Tweetable abstract: Category III tracings are not uncommon prior to delivery among fetuses who develop neonatal encephalopathy. Tweetable abstract: Category III tracings are not uncommon prior to delivery among fetuses who develop neonatal encephalopathy.